2022
DOI: 10.18805/ijar.bf-1493
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Melatonin Receptor Genes Expression in Embryonic Goose Skin Feather Follicles

Abstract: Background: In recent years, it has been reported that melatonin plays an important role in the development of skin hair follicles in mammals. The down we often use is mainly from the skin feather follicles of geese, but their production is not high. Therefore, the study of skin feather follicles is of great significance. Methods: The skin feather follicle tissues of goose dorsal skin at three developmental nodes (E14, E18 and E28) were collected; the differential expression and distribution of melatonin recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In recent years, more and more molecular mechanisms of feather follicle development in poultry have been studied. For example, based on fluorescence quantitative PCR, Western blot and immunohistochemistry, the results showed that the melatonin receptor gene plays an important role in the development of feather follicles in goose skin ( Li, et al, 2022 ). Using Western blot, it was shown that methionine can promote feather follicle development in chicken embryos by activating the Wnt/β-catenin signaling pathway ( Chen, et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more molecular mechanisms of feather follicle development in poultry have been studied. For example, based on fluorescence quantitative PCR, Western blot and immunohistochemistry, the results showed that the melatonin receptor gene plays an important role in the development of feather follicles in goose skin ( Li, et al, 2022 ). Using Western blot, it was shown that methionine can promote feather follicle development in chicken embryos by activating the Wnt/β-catenin signaling pathway ( Chen, et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%